Strategic integration of sustainable development goals in international business: A framework for competitive advantage - Ateeq, Karamath; Agarwal, Sugandha; Jawabr, Adnan; Oswal, Nidhi; Alami, Rachid (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates how multinational enterprises strategically integrate the United Nations Sustainable Development Goals (SDGs) into corporate strategy to attain sustainable competitive advantage. Studies emphasize that SDG alignment enables firms to balance profitability with environmental and social imperatives. The research adopts a qualitative methodology anchored in interpretivism, employing a 90-day multiple case study of Unilever, IKEA, and Safaricom, selected via purposive sampling based on demonstrated SDG integration and global operations. Content analysis of sustainability reports, peer-reviewed publications, and industry frameworks provided robust secondary data. Findings reveal that firms operate the SDGs through ESG-aligned metrics, circular business models, digital innovations, and multi-stakeholder partnerships. For example, IKEA’s circular economy strategy and Safaricom’s mobile financial inclusion platform significantly advanced SDGs 7, 12, and 8, respectively. Key challenges include regulatory fragmentation, short-termism, and supply chain inconsistencies. The study concludes that SDG integration is a strategic imperative and recommends performance-based metrics, cross-sector alliances, and capacity-building for sustainable transformation. These findings offer a replicable framework for global firms navigating sustainable development imperatives.